Causes and consequences of external labor migration in Ukraine (on the example of Ivano-Frankivsk region) - MykhailіukAngela; Rovenchak, Ivan (Human Geography Journal, 2021)
Migration processes of the XXI century have a significant impact on the development of civil society in Ukraine, as they are characterized by large scale. These processes affect the formation of socio-demographic, economic, political and cultural spheres. In Ivano-Frankivsk region, as in the border area, they are quite dynamic. Coverage of migration processes, in particular, labor migration, during the economic crisis, social instability and hostilities in the country and served as a study of the chosen topic of scientific publication. Based on the methods of analysis and synthesis, the main causes and consequences of migration processes in Ivano-Frankivsk region are analyzed. The authors noted the influence of geographical, social and personal factors on the intensification of external migration, and also noted that the economic factor is predominant. In the scientific work for the first time a thorough analysis of the financial condition of citizens of Ukraine in the calculation of the level of the minimum wage in Ivano-Frankivsk region and within Ukraine, in general. Wages were also compared and their differences between Ukraine and a number of European countries, in particular, in Germany, Poland, the Czech Republic, Hungary, and Lithuania. The number of migrants by all types of migration flows during the last year within the Ivano-Frankivsk region is graphically represented by gender. It is established that the majority of migrants are women. Also an important place in the study was the analysis of migration from 2002 to 2019. In the article highlighting the dynamics of these processes, a comparative analysis of the definition of migration. The authors propose the main steps to improve migration policy, namely: the formation of a clear regional program in the field of migration processes, which will ultimately form the basis for sustainable economic development of the region, wage growth (including minimum wage), increase the employed population (respectively, reducing the number of unemployed), as well as replenishment of local budgets through taxes. The current state of external migration within Ivano-Frankivsk is analyzed. It was revealed that against the background of complex socio-economic reforms in the region there was a reduction in the migration flow of the local population in Ivano-Frankivsk region.